Merger control procedure: comparative analysis of the role of court and agencies in the EU and US - Lukjane, Anna (Riga Graduate School of Law, 2021)
This study considers merger control procedure both the procedure itself, reviewing the steps of the procedure, as also analyses the role of procedure’ bodies which are the main actors and which conduct the investigation process, namely the merger control agencies and the court, in both the United States and the European Union. The aim of this study consists in identifying what the role courts and merger control agencies plays during the merger control procedure, in order to understand if there exist instability between these bodies and if the existence of such inevitable cooperation between these bodies influence the effectiveness of the merger control procedure decision-making process. This study is recommended for each who is interested in how the merger control procedure is carried out step by step in the United States and in the European Union, as also in the internal work of the merger control agencies, which are involved and are the main bodies in a merger transaction review.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Competition law